Manajemen Penerapan Sistem Gadai Emas Pada Unit Pegadian Syariah Bonder Kantor Cabang Renteng Lombok Tengah - ratna, ratnawati (UIN Mataram, 2023)
Gadai Emas is the provision of funds to customers using pawn financing that can meet the financial needs of customers by using gold as collateral for financing. This study aims to describe the application of the Gold Pawn System at PT. Pegadaian Syariah Renteng branch office as well as describe the constraints faced by PT. Pegadaian Syariah Renteng Branch Office is in the process of beingimplemented. This research is a field research, which is descriptive qualitative by conducting in-depth interviews with PT. Pegadaian Syariah, the data is then analyzed and produces conclusions. From the results of the study, it can be explained that in its application it has implemented easy steps but still in accordance with existing operational standards, including; through the stages of submitting financing, stages of estimating gold as collateral, stages of disbursement of financing funds, stages at maturity and stages at the time of repayment. Meanwhile, the obstacles that are often faced are due to difficulties in communicating with customers who cannot make payments and face complaints from customers on collateral items.